Infections due to multidrug‐resistant organisms following heart transplantation: Epidemiology, microbiology, and outcomes. Issue 1 (12th December 2019) - Bhatt, Pinki J.; Ali, Mohsin; Rana, Meenakshi; Patel, Gopi; Sullivan, Timothy; Murphy, Joseph; Pinney, Sean; Anyanwu, Anelechi; Huprikar, Shirish; Taimur, Sarah
Abstract: Background: Infections secondary to multidrug‐resistant organisms (MDRO) have emerged as a growing problem in solid organ transplantation (SOT). Most of the published data on MDRO infections in SOT pertains to abdominal organ transplantation and data specific to heart transplantation (HT) are limited. Methods: This is a retrospective review of HT recipients at our institution from 2011 to 2016; with the aim to investigate the epidemiology, microbiologic spectrum, and outcomes in patients with post‐HT MDRO infections, classified as multidrug‐resistant (MDR), extensively drug‐resistant (XDR), and pandrug‐resistant (PDR) using standardized definitions. Results: Of the 149 HT recipients, 82 episodes of bacterial infection were seen in 46 patients (31%) in the year following HT. Thirty (37%) were due to MDR pathogens and 13 (16%) were XDR. The most common gram‐negative MDR pathogens were extended‐spectrum beta‐lactamase (ESBL) Escherichia coli and Klebsiella pneumoniae ; while XDR pathogens were most commonly Pseudomonas aeruginosa followed by carbapenem‐resistant Klebsiella pneumoniae . Majority of infection episodes were bloodstream (54, 66%) followed by pulmonary infection (20, 24%). Within a year after transplant, HT recipients with any bacterial infection had significantly higher mortality versus those without infection; and XDR infections were associated with a 26‐fold greater hazard of death on average compared to those without infection (adjusted HR, 26.1; 95% CI, 6.4‐107.0; P  < .001). There were no PDR infections. Conclusion: Bacterial infections were a significant predictor of 1‐year post‐HT mortality, which was highest among those with XDR infections. This study highlights the burden of MDRO infections in HT recipients and identifies an area of future research.